Ensaios - I (Compilação de Textos, Comentários, Palestras e Conferências - entre 2007 e 2018) - Almeida, E. C. (2025)
Abstract: This book (essay) contains several texts presented in Conferences, Lectures and Communications, most of them scientific in nature, which took place between 2007 and part of 2018. It has a Preface by Prof. Doctor Celso D. J. Malavoloneke entitled «(Essays; a flight of anthropological humbihumbi1)» 1-humbihumbi: bird from Unbundu mythology (Angola) that is characterized by its ability to fly very high due to the lightness of its structure. It serves to exemplify how humility and modesty give greatness to people.